Our Public Health History in Florida: Interview with Donna J. Petersen - Robert J. McDermott (University of North Florida, 2005)
Donna J. Petersen, MHS, ScD began her tenure as the fourth Dean of the University of South Florida College of Public Health on November 1, 2004. Prior to joining USF, she was Professor in the Departments of Maternal and Child Health, and Health Care Organization and Policy at the University of Alabama at Birmingham (UAB), School of Public Health. From 1996 to 2003, she was the senior associate dean for academic affairs at the UAB School of Public Health. From 1990 to 1995, she served as Director of the Division of Family Health at the Minnesota Department of Health. Dr. Petersen earned her masters and doctoral degrees from the Johns Hopkins School of Public Health. She has also held positions with the federal government and the state of Maryland and has served on numerous community agency boards and gubernatorial commissions and task forces. While in Minnesota, she served as adjunct faculty at the University of Minnesota School of Public Health. She has been a frequent lecturer on topics related to maternal and child health, health care reform, and systems change and leadership, and has provided extensive technical assistance and training to state health departments in the areas of needs assessment, data system development, and public health roles within evolving health care systems. She has devoted particular attention to public health responsibilities in monitoring health status, access, utilization, and quality of health care and in the areas of systems level accountability and the development of population-based indicators. She is the author of numerous publications, book chapters and a textbook on needs assessment in public health. She has been honored for her work by the American Public Health Association, the Association of Teachers of Maternal and Child Health, the National Healthy Mothers, Healthy Babies Coalition, and the Delta Omega National Public Health Honor Society. She was the 1996 recipient of the UAB President's Excellence in Teaching Award and is the 2003 recipient of the UAB School of Public Health Outstanding Public Health Service Award. This interview took place between May 18, 2005 and June 2, 2005.